Analisis Kualitas Pelayanan Publik Pada Perusahaan Umum Daerah Air Minum (Pudam) Tirta Katong Ponorogo (Studi Kasus Pada Konsumen Pudam Tirta Katong Ponorogo) - Yudha Prasetya Wardana; Mai Puspadyna Bilyastuti; Anton Subagyo (UNIVED PRESS, Universitas Dehasen Bengkulu, 2026)
This research is motivated by the increasing competition in the public service sector, which requires companies to formulate effective marketing strategies to maintain business continuity and achieve competitive advantage. The main focus of the research is to fulfill customer expectations regarding the quality of public services at the Regional Drinking Water Company (PUDAM) Tirta Katong Ponorogo, with the aim of analyzing factors that influence customer satisfaction and loyalty, assessing service quality, identifying problems, and reviewing the company's handling efforts. This research uses a qualitative approach with a purposive sampling method. Data were collected through observation, direct interviews with employees and customers, and documentation. The research findings indicate that PUDAM Tirta Katong Ponorogo's services have not reached optimal levels, mainly due to the low responsiveness and empathy of officers in serving customers. The main problems found include disruptions in water distribution, cloudy and smelly water quality, and unstable water supply, which are the biggest obstacles triggering an increase in the number of customer complaints. As an effort to improve service quality, especially in handling complaints, PUDAM Tirta Katong Ponorogo has provided a complaint facility through official social media, carried out routine monthly checks, and implemented a District Meter Area (DMA) system to prevent and detect water theft. Through these steps, it is hoped that problems with water availability and quality can be minimized through regular monitoring and checks carried out appropriately and evenly, so that the quality of service can be maintained properly.